Predator kills the Marvel Universe - Percy, Benjamin (Marvel Worldwide, Inc., 2026)
"A Predator King, emboldened by a new vibranium arsenal and aided by a surprising human ally, launches an all-out invasion of Earth, claiming the planet as a hunting preserve! After several battles in our solar system -- which devastate both the Guardians of the Galaxy and the Fantastic Four -- the Predators escalate to the next stage of their war. And the X-Men and the Avengers are at the top of their kill list! Who will survive this extinction-level event as the entire Marvel Universe finds itself in the tri-laser crosshairs of the Predators?!"--